Computer simulation study of a direction finding algorithm - Ong, Andy Liang Wei (2015)
The use of an antennas array enables spatial diversity. Such diversity allows the direction of a signal to be estimated. The aim of this project is to study the design of a direction-of-arrival (DOA) estimation algorithm, multiple signal classification (MUSIC), and evaluate its performance via computer simulation in Matrix Laboratory (MATLAB). Essentially, DOA estimation algorithm forms the brain of an antenna array, processing the data received from the incident signals to extract DOA information. A total of eight parameters is identified, tested and analyzed for this final year project. This offers a holistic view of the ability of MUSIC algorithm in DOA estimation. It is observed that not all factors are equal, some of the factors have more substantial impact on the accuracy and resolution of the DOA estimation than the others. The degree of influence of each parameters is being analyzed and evaluated. MUSIC algorithm is observed to be sensitive to the changes in the following parameters: signal-to-noise ratio (SNR), array elements spacing and angle of separation of the signals. Hence, further testing can be done to analyze the impact of these factors and try to adjust the controllable parameters to reduce the DOA estimation error in future application.